Preservasi Pakan dengan Teknologi Ensilase untuk Optimalisasi Ketersediaan Bahan Pakan Ternak Hijauan di Desa Ngasem Kecamatan Ngajum Kabupaten Malang - Alfi Fadliana; Priska Choirina; Bella Cornelia Tjiptady; Indah Martha Fitriani; Candra Pradhana (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2021)
The tendency of traditional grass-finding methods and the limited availability of forage fodder for ruminants during the dry season are the main obstacles faced by livestock keepers in Ngasem Village, Ngajum District, Malang Regency. One of the efforts made in this community service activity is to provide knowledge and skills of feed preservation through the ensilage method by utilizing agricultural waste and local grass plants. The purpose of this activity is to increase the understanding of livestock farmers regarding the nutritional needs of ruminants, ensure the availability of animal feed throughout the season, and improve the welfare of the livestock farming community. The forms of community service activities consist of: 1) socialization of ensilase technology and the use of agricultural waste, 2) demonstration/practice of making fermented animal feed with ensilase technology, and 3) post-socialization assistance and demonstration of making ensilage animal feed. The results of the activity showed an increase in public knowledge about making feed preservation with ensilage technology as well as optimizing the use of agricultural waste and local forage plants as a reserve for the availability of ruminant feed. This can be seen from the level of participation and enthusiasm of livestock farmers in participating in a series of educational activities.